POSSIBILITIES FOR ALLEVIATING UNWANTED BEHAVIOR PROBLEMS FOR 4TH-6TH GRADE STUDENTS - Kalēja, Lelde (Education Reform: Education Content Research and Implementation Problems, 2024)
The aim of this scientific article is to present the development of a comprehensive methodology for the prevention of student behavior disorders, focusing on the reasons that contribute to their occurrence. The development of this methodology is based on research that analyzes the risk factors associated with behavioral disorders in students, studying the interaction between individual, family and environmental factors.The article will discuss about methodological components, including early identification and intervention, social-emotional learning programs, positive behavior support systems, and collaboration between educators, parents, and mental health professionals. The findings will include recommendations for improving programs designed to prevent unwanted behavior.